Cardiovascular and non-cardiovascular hospital admissions associated with atrial fibrillation: a Danish nationwide, retrospective cohort study - Christiansen, Christine Benn (BMJ Publishing Group, 2013)
OBJECTIVE: To examine the excess risk of hospitalisation in patients with incident atrial fibrillation (AF). DESIGN: A nationwide, retrospective cohort study. SETTING: Denmark. PARTICIPANTS: Data on all admissions in Denmark from 1997 to 2009 were collected from nationwide registries. After exclusion of subjects previously admitted for AF, data on 4 602 264 subjects and 10 779 945 hospital admissions contributed to the study. PRIMARY AND SECONDARY OUTCOME MEASURES: Age-stratified and sex-stratified admission rates were calculated for cardiovascular and non-cardiovascular admissions. Temporal patterns of readmission, relative risk and duration of frequent types of admission were calculated. RESULTS: Of 10 779 945 hospital admissions, 729 088(6.8%) were associated with AF. Admissions for cardiovascular reasons after 1, 3 and 6 months occurred for 6.0, 14.3 and 28.4% of AF patients versus 0.2, 0.6 and 1.8 of non-AF patients. Admissions for non-cardiovascular reasons after 1, 3 and 6 months comprised 6.8, 16.1 and 33.3% of AF patients and 1.2, 3.2 and 9.7% of non-AF patients. When stratified for age, AF was associated with similar cardiovascular admission rates across all age groups, while non-cardiovascular admission rates were higher in older patients. Within each age group and for both cardiovascular and non-cardiovascular admissions, AF was associated with higher rates of admission. When adjusted for age, sex and time period, patients with AF had a relative risk of 8.6 (95% CI 8.5 to 8.6) for admissions for cardiovascular reasons and 4.0 (95% CI 4.0 to 4.0) for admission for non-cardiovascular reasons. CONCLUSIONS: This study confirms that the burden of AF is considerable and driven by both cardiovascular and non-cardiovascular admissions. These findings underscore the importance of using clinical and pharmacological means to reduce the hospital burden of AF in Western healthcare systems.